(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Topics devoted to the theoretical foundations and priorities of security and technology science are covered. These topics describe the essence of security and technology concepts, threshold parameters for security detection and assessment, security and technology mechanisms, micro-programs and instructions